2015
DOI: 10.1016/j.amepre.2015.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Gestational Diabetes Among Hospital Deliveries in 19 U.S. States, 2000–2010

Abstract: Introduction Diabetes is one of the most common and fastest-growing comorbidities of pregnancy. Temporal trends in gestational diabetes mellitus (GDM) have not been examined at the state level. This study examines GDM prevalence trends overall and by age, state, and region for 19 states, and by race/ethnicity for 12 states. Sub-analysis assesses trends among GDM deliveries by insurance type and comorbid hypertension in pregnancy. Methods Using the Agency for Healthcare Research and Quality’s National and Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 25 publications
6
53
0
Order By: Relevance
“…Whereas pre-pregnancy underweight and insufficient gestational weight gain, which have been linked to restricted fetal growth, will result in an increased risk of childhood cancers that have been associated with lower birthweight [27, 28, 32]. Given the increasing prevalence of obesity and overweight status among women of childbearing age and increasing rates of pre-pregnancy and gestational diabetes deliveries in the US [33–35], we aim to assess the association between pre-pregnancy diabetes, gestational diabetes, pre-pregnancy BMI, and gestational weight gain on the risk of all childhood cancers before age 6 in a very large, diverse and population-based sample of children born in California, in which Hispanics are the dominant ethnicity.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas pre-pregnancy underweight and insufficient gestational weight gain, which have been linked to restricted fetal growth, will result in an increased risk of childhood cancers that have been associated with lower birthweight [27, 28, 32]. Given the increasing prevalence of obesity and overweight status among women of childbearing age and increasing rates of pre-pregnancy and gestational diabetes deliveries in the US [33–35], we aim to assess the association between pre-pregnancy diabetes, gestational diabetes, pre-pregnancy BMI, and gestational weight gain on the risk of all childhood cancers before age 6 in a very large, diverse and population-based sample of children born in California, in which Hispanics are the dominant ethnicity.…”
Section: Introductionmentioning
confidence: 99%
“…21 Among delivery hospitalizations, the prevalence of GDM increased more quickly than preexisting diabetes from 2000 to 2010; GDM prevalence increased 56% while preexisting diabetes increased 37%. 26 Several studies have found that racial/ethnic minority women, especially Asian and Hispanic women, have a higher prevalence of GDM than non-Hispanic white women. 24,2628 Further, women who experienced GDM are 50%–80% more likely to develop GDM in a subsequent pregnancy, 10 and even without GDM recurrence in the subsequent pregnancy, offspring from subsequent pregnancies are more likely to experience adverse health outcomes compared to offspring of mothers who never had GDM.…”
Section: Introductionmentioning
confidence: 99%
“…26 Several studies have found that racial/ethnic minority women, especially Asian and Hispanic women, have a higher prevalence of GDM than non-Hispanic white women. 24,2628 Further, women who experienced GDM are 50%–80% more likely to develop GDM in a subsequent pregnancy, 10 and even without GDM recurrence in the subsequent pregnancy, offspring from subsequent pregnancies are more likely to experience adverse health outcomes compared to offspring of mothers who never had GDM. 29 A major challenge to surveillance of GDM is that screening practices and diagnostic thresholds for identifying women with GDM may vary by institution, which makes it difficult to determine whether changes in prevalence estimates reflect variation in clinical practice or true changes in the proportion of women with GDM.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to ethnicity, there are other health factors that can increase one's risk of developing GDM, such as age greater than 25 years, those with a family history of diabetes, GDM in a previous pregnancy, chronic hypertension, centripetal obesity, Polycystic Ovary Syndrome (PCOS), and high fasting glycemia in the first trimester [4]. The U.S. Preventative Services Task Force also recommends screening asymptomatic pregnant women after 24 weeks of gestation [5].…”
Section: Screeningmentioning
confidence: 99%